Chorea and the effectiveness of steroids in a patient with the syndrome of transient headache with neurologic deficits and cerebrospinal fluid lymphocytosis: A case report - Zhao, Lu; Wang, Ruihao; Fang, Hui; Song, Bo; Liang, Dongyi; Xu, Yuming (Journal of Pain Research, 2019)
Background: The clinical manifestations of the transient headache and neurologic deficits with cerebrospinal fluid lymphocytosis (HaNDL) syndrome are variable, and involuntary movements have not been reported. The etiology and treatment of the syndrome are not entirely clarified. Case: A 25-year-old female presented with recurrent transient headache, involuntary movements (left upper extremity chorea) and paralysis. Lumbar punctures showed intracranial hypertension and cerebrospinal fluid pleocytosis. Symptoms and intracranial hypertension were relieved after administration of steroids. Discussion/conclusion: Chorea may also present in the HaNDL syndrome. Steroids might relieve the symptoms of the HaNDL syndrome, which indicates the possible treatment strategy for HaNDL and supports the infectious or postinfectious autoimmune etiology hypothesis.
CRIS-Team Scopus Importer:2019-08-06
Keywords: Intracranial hypertension; Involuntary movement; Steroids; Syndrome of transient headache and neurological deficits with cerebrospinal fluid lymphocytosis (HaNDL)